2013
DOI: 10.1016/s2213-2600(13)70126-7
|View full text |Cite
|
Sign up to set email alerts
|

Diet and asthma: vitamins and methyl donors

Abstract: SUMMARY Dietary changes may partly explain the high burden of asthma in industrialized nations. Experimental studies have motivated a significant number of observational studies of the relation between vitamins (A, C, D, and E) or nutrients acting as methyl donors (folate, vitamin B12, and choline) and asthma. Because observational studies are susceptible to several sources of bias, well-conducted randomized controlled trials (RCTs) remain the “gold standard” to determine whether a vitamin or nutrient has an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 117 publications
2
52
0
5
Order By: Relevance
“…Compared with obese women without asthma, obese women with asthma have increased macrophage infiltration, higher expression of leptin, and lower expression of adiponectin in adipose tissue (42). Other proposed mechanisms include presence of comorbidities (43,44), hormonal differences (45), dietary pattern changes (46,47), and alterations in insulin or arginine metabolism (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with obese women without asthma, obese women with asthma have increased macrophage infiltration, higher expression of leptin, and lower expression of adiponectin in adipose tissue (42). Other proposed mechanisms include presence of comorbidities (43,44), hormonal differences (45), dietary pattern changes (46,47), and alterations in insulin or arginine metabolism (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E has been proved to have the capabilities of rescuing allergen-induced inhibition of antioxidant enzymes, preventing the detrimental effects of air pollution as well as asthmatic features in asthma [3][4][5]. Furthermore, it has also been concluded that vitamin E supplements could improve clinical manifestations and pulmonary function tests in children with moderate asthma [6].…”
mentioning
confidence: 99%
“…Epigenetic mechanisms, including DNA methylation [81,82], histone modifications, and noncoding RNAs, can affect gene transcription [83].…”
Section: Effects Of Diet On Epigenetic Regulation In Bronchial Asthmamentioning
confidence: 99%